Epstein–Barr virus status of sporadic Burkitt lymphoma is associated with patient age and mutational features. (6th October 2021) - Richter, Julia; John, Katharina; Staiger, Annette M.; Rosenwald, Andreas; Kurz, Katrin; Michgehl, Ulf; Ott, German; Franzenburg, Sören; Kohler, Christian; Finger, Jasmin; Oschlies, Ilske; Paul, Ulrike; et al.
Summary: Sporadic Burkitt lymphoma (BL) is the most frequent tumour of children and adolescents but a rare subtype of lymphomas in adults. To date most molecular data have been obtained from lymphomas arising in the young. Recently, Epstein–Barr virus (EBV) positive and negative BL in young patients was shown to differ in molecular features. In the present study, we present a large age‐overarching cohort of sporadic BL ( n  = 162) analysed by immunohistochemistry, translocations of MYC proto‐oncogene, basic helix‐loop‐helix transcription factor ( MYC ), B‐cell leukaemia/lymphoma 2 ( BCL2 ) and B‐cell leukaemia/lymphoma 6 ( BCL6 ) and by targeted sequencing. We illustrate an age‐associated inter‐tumoral molecular heterogeneity in this disease. Mutations affecting inhibitor of DNA binding 3, HLH protein ( ID3 ), transcription factor 3 ( TCF3 ) and cyclin D3 ( CCND3 ), which are highly recurrent in paediatric BL, and expression of sex determining region Y‐box transcription factor 11 (SOX11) declined with patient age at diagnosis ( P  = 0·0204 and P  = 0·0197 respectively). In contrast, EBV was more frequently detected in adult patients ( P  = 0·0262). Irrespective of age, EBV‐positive sporadic BL showed significantly less frequent mutations in ID3 / TCF3 / CCND3 ( P  = 0·0088) but more often mutations of G protein subunit alpha 13 ( GNA13 ; P  = 0·0368) and forkhead box O1 ( FOXO1 ; P  = 0·0044) compared to EBV‐negative tumours. Our findings suggest that among sporadic BL an EBV‐positive subgroup of lymphomas increases with patient age that shows distinct pathogenic features reminiscent of EBV‐positive endemic BL.